2004
DOI: 10.3727/000000004783983369
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison between Real-Time Quantitative PCR and DNA Hybridization for Quantitation of Male DNA following Myoblast Transplantation

Abstract: The transplantation of muscle precursor cells (myoblasts) is a potential therapy for Duchenne muscular dystrophy. A commonly used method to detect cell survival is quantitation of the Y chromosome following transplantation of male donor cells into female hosts. This article presents a direct comparison between real-time quantitative PCR (Q-PCR) and the DNA hybridization (slot-blot) technique for quantitation of Y chromosome DNA. Q-PCR has a significantly greater linear quantitation range and is up to 40-fold m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…loss of long-term expression of the marker in surviving cells (146,203,256), leakage of marker and subsequent uptake by host cells, toxicity from chronic exposure of markers, change in cellular distribution over time, and uptake/redistribution by scavenging host microglia/macrophages. Other markers may circumvent these factors by the use of species-specific markers, markers associated with a specific gene promoter or adenoviral (AdV), adeno-associated viral (AAV), retroviral (RV), and lentiviral (LV) vectors for the introduction of foreign genes encoding either the bacterial marker enzyme β-galactosidase/LacZ or green fluorescent protein (GFP), fluorescent (usually rhodamine or fluorescein) dye-coated latex microspheres/beads/nanospheres, and combined analysis with other assays such as IHC, retrograde-labeling, or EM, FISH, or real-time quantitative PCR using donor-specific sequences [e.g., Y1 DNA of male cells transplanted into female hosts (34,134), as well as the use of thymidine, bromodeoxyuridine (BrdU), and ethynyl deoxyuridine (EDU) analogues (133)].…”
Section: Ipsc-based Therapies As a Candidate For Sci Repairmentioning
confidence: 99%
“…loss of long-term expression of the marker in surviving cells (146,203,256), leakage of marker and subsequent uptake by host cells, toxicity from chronic exposure of markers, change in cellular distribution over time, and uptake/redistribution by scavenging host microglia/macrophages. Other markers may circumvent these factors by the use of species-specific markers, markers associated with a specific gene promoter or adenoviral (AdV), adeno-associated viral (AAV), retroviral (RV), and lentiviral (LV) vectors for the introduction of foreign genes encoding either the bacterial marker enzyme β-galactosidase/LacZ or green fluorescent protein (GFP), fluorescent (usually rhodamine or fluorescein) dye-coated latex microspheres/beads/nanospheres, and combined analysis with other assays such as IHC, retrograde-labeling, or EM, FISH, or real-time quantitative PCR using donor-specific sequences [e.g., Y1 DNA of male cells transplanted into female hosts (34,134), as well as the use of thymidine, bromodeoxyuridine (BrdU), and ethynyl deoxyuridine (EDU) analogues (133)].…”
Section: Ipsc-based Therapies As a Candidate For Sci Repairmentioning
confidence: 99%
“…As human TTN gene (367 exons, localized on 2q31) is present as only one single copy in the cell, it has been chosen to permit a direct correlation with the number of cells. Selecting a gene located on an autosomal chromosome, instead of using a probe recognising Y chromosome [15], extends our approach to human cells, isolated from both male and female subject. To ensure that our primers recognize exclusively genomic DNA sequences, we designed the couple of primers in the intron 1 of the human gene.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have been reported using RT-PCR to detect donor cells in transplantation models 910 . Dr. Schwarzenberger’s group first developed a murine bone marrow transplantation model using real-time PCR to amplify y-chromosome-specific 8 .…”
Section: Discussionmentioning
confidence: 99%